2013
DOI: 10.1007/s00380-013-0389-z
|View full text |Cite
|
Sign up to set email alerts
|

Ablation of swallowing-induced atrial tachycardia affects heart rate variability: a case report

Abstract: A 47-year-old man underwent slow pathway ablation for slow-fast atrioventricular nodal reentrant tachycardia. Following the procedure, he felt palpitations while swallowing, and swallowing-induced atrial tachycardia was diagnosed. Swallowing-induced atrial tachycardia arose from the right atrium-superior vena cava junction and was cured by catheter ablation. After the procedure, the patient's heart rate variability changed significantly, indicating suppression of parasympathetic nerve activity. In this case, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 14 publications
0
18
0
Order By: Relevance
“…The HF component was solely suppressed after ablation with suppression of APCs, suggesting that parasympathetic nerve activity was strongly involved in the cause of this arrhythmia rather than the sympathetic nerve system. Since AT was suppressed by ablation at a single site, not by SVC isolation, the success site might be the end of axons from ganglionated plexi (possibly the SVC–aorta ganglionated plexi), which contained mainly the parasympathetic nerve system, as previously reported 10, 11…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…The HF component was solely suppressed after ablation with suppression of APCs, suggesting that parasympathetic nerve activity was strongly involved in the cause of this arrhythmia rather than the sympathetic nerve system. Since AT was suppressed by ablation at a single site, not by SVC isolation, the success site might be the end of axons from ganglionated plexi (possibly the SVC–aorta ganglionated plexi), which contained mainly the parasympathetic nerve system, as previously reported 10, 11…”
Section: Discussionmentioning
confidence: 69%
“…They also described that the most possible mechanism was a vagally mediated neural reflex involving a neurotransmitter other than acetylcholine because atropine and bethanechol did not affect the swallowing-induced AT. Recently, many other reports suggested a neural reflex as the cause of swallowing-induced AT 8, 9, 10, 11…”
Section: Discussionmentioning
confidence: 99%
“…Hojo et al reported that the mechanism of SIAT might be related to the stimulation of cardiac autonomic ganglionated plexi (GPs) (11). The cardiac GPs are a part of the intrinsic cardiac autonomic nervous system and contain clusters of autonomic ganglia.…”
Section: Discussionmentioning
confidence: 99%
“…Most frequently, an ectopic focus is present in the left atrium, and it is very often pulmonary vein mediated 1 . The observation, however, of an origin in the low posterior right atrium 1 or from the superior caval vein demonstrates that there is no predisposed region of this kind of AT 2 . Among the mechanisms that may explain swallowing-induced AT are:

Direct stimulation of the left atrium by the passage of contents or contraction of the esophagus.

…”
Section: Case Evaluationmentioning
confidence: 99%